Public policy in the city of Buenos Aires aimed at vulnerable youth. Continuities and transformations in the last decade - Raggio, Liliana (2012)
As part of broader research on public policy aimed at vulnerable youth in the City of Buenos Aires, this article discusses a set of programs based on diagnosis regarding urban “insecurity” in general, and youth at risk in particular. Specifically, it addresses the so-called “Crime Prevention Plan” and various actions of cultural policy, reflecting on their characteristics and possible convergence, which bring into play social representations regarding the relationship between crime, culture and vulnerable youth. Through case studies and considering public policy recommendations aimed at youth from various international agencies and institutions, the emphasis and agendas of our own Latin American region are underlined, in relation to recent political changes and socio-cultural consequences of neoliberal policies in the region.